Democracy of Deeds and Voices - CHAN, David (Institutional Knowledge at Singapore Management University, 2014)
In an invited commentary, SMU Behavioural Sciences Institute Director Professor David Chan discussed the nature of a negativity mindset and how to foster positivity in Singapore. He suggested that Singapore should be a “democracy of deeds and voices” and build psychological capital as a core resource.